Comprensión de conceptos físicos mediante exhibiciones interactivas: un estudio comparativo - Sebastià, José M. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
In this work we tried to find relationships between the variables of gender, age, aptitude, previous attitude and learning of a sample of 126 students between the ages of 14 and 16 in a visit to the Museo de los Ninos, Caracas, Venezuela. We also carried out a comparative study between learning at the Museum and learning in a traditional classroom lecture, for two different groups. An Analysis of Variance showed a significant relation between previous attitude and age (inverse) and student learning. No significant differences were found between genders in the post test. Results show that the visit to the Museum was found to be more effective on learning than the classroom lecture. However, no differences were found between groups subjected to opposite order of treatment (Museum-Classroom lecture) through a counter-balance design approach.